Morphological characterization, statistical modeling and wear behavior of AA7075-Titanium Carbide-Graphite surface composites via Friction stir processing - Namdev Ashok Patil; Srinivasa Rao Pedapati; Othman Mamat; Abdul Munir Hidayat Syah Lubis (Journal of Materials Research and Technology, 2021)
In this study, the wear behavior of AA7075-T6 has been significantly improved by encapsulating TiC and graphite nanoparticles using FSP. The wear tracks and debris SEM EDX analysis confirms that the prominent wear mechanism changed from fretting fatigue to abrasion due to the presence of TiC/Gr mechanically mixed layer at contacting surfaces. The tool rotational speed-w rpm (39%), TiC/Gr vol% (14%), the interaction effect of tool rotational speed and TiC/Gr hybrid ratio HR (17%) and interaction effect of tool traverse speed v-mm/min and vol% (23%) observed to be most influential factors. The lowest wear rate was observed for the Run 19 surface composite produced at lower rotational, traverse speeds and with higher volume percentage TiC/Gr with the weight ratio of 60:40. The ranges of parameters that hold suitable for retaining the inherent precipitates along with the dispersion of graphitized-TiC particles have been traced successfully, and the prediction equation of wear rate is defined. Subsequently, it has been validated through observed confirmation results. The predicted and experimental values showed a good association. The inherent isomorphous precipitates dissolution due to excessive intense plasticization has been confirmed through FESEM analysis. The interfacial bonding of TiC/graphite nanoparticles with the base alloy matrix was found to be the necessary condition in controlling the wear rate. The composites processed at lower tool stirring parameters have resulted in good wear properties since it retained inherent precipitates along with the dispersion of graphitized-TiC particles. The wear rate was found to be a function of graphite content inside composites.